Functional Food Targeting the Regulation of Obesity-Induced Inflammatory Responses and Pathologies - Shizuka Hirai; Nobuyuki Takahashi; Tsuyoshi Goto; Shan Lin; Taku Uemura; Rina Yu; Teruo Kawada (Mediators of Inflammation)
Obesity is associated with a low-grade systemic chronic inflammatory state, characterized by the abnormal production of pro- and anti-inflammatory adipocytokines. It has been found that immune cells such as macrophages can infiltrate adipose tissue and are responsible for the majority of inflammatory cytokine production. Obesity-induced inflammation is considered a potential mechanism linking obesity to its related pathologies, such as insulin resistance, cardiovascular diseases, type-2 diabetes, and some immune disorders. Therefore, targeting obesity-related inflammatory components may be a useful strategy to prevent or ameliorate the development of such obesity-related diseases. It has been shown that several food components can modulate inflammatory responses in adipose tissue via various mechanisms, some of which are dependent on peroxisome proliferator-activated receptor γ (PPARγ), whereas others are independent on PPARγ, by attenuating signals of nuclear factor-κB (NF-κB) and/or c-Jun amino-terminal kinase (JNK). In this review, we introduce the beneficial effects of anti-inflammatory phytochemicals that can help prevent obesity-induced inflammatory responses and pathologies.